Sex differences in associations of arterial compliance with coronary artery plaque and calcification burden - Coutinho, T.; Yam, Y.; Dwivedi, Girish; Inácio, J.; Chow, B. (Wiley-Blackwell, 2017)
© 2017 The Authors and Medtronic. Background--Coronary artery disease is a leading killer of women. Arterial stiffness predicts myocardial infarction, and postmenopausal women have lower arterial compliance (AC) than men. We hypothesized that lower AC would be associated with greater burden of coronary artery plaque and calcification, and that these associations would be stronger in women than men. Methods and Results--We evaluated 3639 consecutive adults without coronary artery disease history who had coronary computed tomography between 2006 and 2014. Coronary artery calcification was calculated using the Agatston method. Plaque extent was assessed by the number of arterial segments with visible plaque divided by the number of visualized segments 9100 (percent plaque score). Indexed AC was calculated as stroke volume index/central pulse pressure. We used step-wise multivariable linear regression to assess associations of log indexed AC with log (percent plaque score+1) and log (coronary artery calcification+1). Sex-specific models were performed if the interaction sex9AC was significant. Mean age was 57±11 years, 53% were men, and 71% were hypertensive. Interaction term sex9AC was significant for both models (P=0.008 for percent plaque score and 0.022 for coronary artery calcification). Lower indexed AC was associated with higher percent plaque score and coronary artery calcification in women (b±SE: ß0.231±0.113, P=0.042 and ß0.334±0.166, P=0.044, respectively), but not in men (b±SE: ß0.062±0.104, P=0.551 and 0.114±0.173, P=0.510, respectively). Conclusions--Lower AC is associated with greater burden of coronary artery plaque and calcification in women, but not in men. Our findings highlight low AC as a correlate of more-advanced coronary artery disease and as a potential link to the worse cardiovascular outcomes in women.